STRUKTUR DAN IMPLEMENTASI DP3 SEBAGAI SISTEM PENILAIAN PEKERJAAN (SEBUAH TINJAUAN TEORITIS) - Kurniati, Dra. Tetty (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2004)
Indonesian civil servants work under the principle of being ?servants of the state and servants of the community?. However, there is a long tradition of convoluted bureaucracy, poor public service deliveries, and inefficient government. The demand for better performance from civil service personnel comes both from national pressure and also from the need to be efficient as dictated by international trade and commerce. As with other developing countries, the government of Indonesia has had difficulty improving the quality of human resources, especially within the public sector. This difficulty does not stem onlyfrom the human factor, but also from within the system itself. This article is a review of the Indonesian Civil Servants? Performance Evaluation Program which is currently being used all over Indonesia as a means of evaluating civil servants? performance. The main feature of the review will be analyzing the DP3 structure and its implementation. The review will also examine the strengths and weaknesses of the DP3 system followed by a series of practical recommendations for consideration by officials to modify the existing system.